Language Property in Speech Acts Language Activities in Speech Program Indonesian Lawyers Club (ILC) TV ONE - Dedi Satriawan (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
This study aims to identify, describe the use of locutionary, illocutionary, and perlocutionary speech acts and describe the deviations from the use of politeness and cooperation principles in the three types of speech acts on the Indonesia Lawyers Club program on TV One episode Is It Necessary to Declare Total War and Badr War using a descriptive-qualitative approach, so that the speech acts used and deviations from the politeness and cooperation principles used by speakers or resource persons in the event can be identified. This study uses a descriptive-qualitative research method, namely by using content analysis techniques. This means that by using this method the data that has been obtained from the video shows is then transcribed and analyzed, described and interpreted with the stated objectives and then concluded. In analyzing the data, a series of activities were carried out, namely 1) data reduction, 2) data presentation, and 3) drawing conclusions. The results of the study show that the most widely used speech act is perlocutionary speech act, and if it is associated with the use of the principles of politeness and cooperation, then most of the speakers violate the maxims of wisdom, humility and consensus. Meanwhile, when viewed from the violation of the principle of cooperation, speakers often violate the maxim of quality and method.